2015
DOI: 10.3389/fnhum.2015.00395
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the translation of intentions into action by implementation intentions: behavioral effects and physiological correlates

Abstract: The present review addresses the physiological correlates of planning effects on behavior. Although intentions to act qualify as predictors of behavior, accumulated evidence indicates that there is a substantial gap between even strong intentions and subsequent action. One effective strategy to reduce this intention–behavior gap is the formation of implementation intentions that specify when, where, and how to act on a given goal in an if-then format (“If I encounter situation Y, then I will initiate action Z!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 132 publications
3
86
0
Order By: Relevance
“…Thus, whereas event cues were processed as a part of the ongoing activity, time cues required the deployment of strategic attentional resources (i.e, monitoring the virtual time of day, which involves internally driven shifting of attention from the ongoing activity) to be processed. Our results support the notion that specification and repetition of PM intentions during encoding heightens perceptual readiness for and facilitates detection of cues encountered in the environment 26,30 , in this case, the event cues. However, heightened cue accessibility would not facilitate detection of time cues in the absence of strategic monitoring (or shifting) because those cues would not be encountered.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Thus, whereas event cues were processed as a part of the ongoing activity, time cues required the deployment of strategic attentional resources (i.e, monitoring the virtual time of day, which involves internally driven shifting of attention from the ongoing activity) to be processed. Our results support the notion that specification and repetition of PM intentions during encoding heightens perceptual readiness for and facilitates detection of cues encountered in the environment 26,30 , in this case, the event cues. However, heightened cue accessibility would not facilitate detection of time cues in the absence of strategic monitoring (or shifting) because those cues would not be encountered.…”
Section: Discussionsupporting
confidence: 85%
“…This aligns with the proposed mechanism of implementation intentions, which is that they promote a shift from controlled to automatic processing. Specifically, they allow intention retrieval to occur in a reflexive, stimulus-driven fashion rather than require self-initiated retrieval processes 26,30 . This notion is supported by an fMRI study showing that implementation intentions shifted brain activity from a region associated with top-down control of PM processing (lateral BA 10) to one associated with bottom-up PM responding (medial BA 10) 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Gollwitzer and colleagues (Gollwitzer, ; Sheeran, Webb, & Gollwitzer, ; Wieber, Thurmer, & Gollwitzer, ) have extensively described the strength and functioning of implementation intentions where individuals specify exactly how and when they will apply new strategies to address an issue. In an initial study in the training domain, Friedman and Ronen () found that sales managers with implementation intentions received higher transfer of training scores than those without such goals.…”
Section: Study Ways To Optimize Impact On Transfermentioning
confidence: 99%